2020
DOI: 10.3389/fpls.2020.00964
|View full text |Cite
|
Sign up to set email alerts
|

Fruit From Two Kiwifruit Genotypes With Contrasting Softening Rates Show Differences in the Xyloglucan and Pectin Domains of the Cell Wall

Abstract: Fruit softening is controlled by hormonal and developmental cues, causing an upregulation of cell wall-associated enzymes that break down the complex sugar matrices in the cell wall. The regulation of this process is complex, with different genotypes demonstrating quite different softening patterns, even when they are closely related. Currently, little is known about the relationship between cell wall structure and the rate of fruit softening. To address this question, the softening of two Actinidia chinensis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 100 publications
0
10
0
Order By: Relevance
“…In this regard, the researchers studied the metabolism of the hemicelluloses of pears in refrigerated storage, determining that in the level of changes correlated with the extension of time in storage [ 61 ]. Similarly, kiwifruit with different softening rates were compared, and it was found that the slow softening genotype showed higher concentrations of glucose and xylose, hemicellulose associated components, in the later stages of softening [ 62 ]. This aspect is relevant, given that in cold storage the cell wall continues to undergo modifications that affect fruit firmness.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the researchers studied the metabolism of the hemicelluloses of pears in refrigerated storage, determining that in the level of changes correlated with the extension of time in storage [ 61 ]. Similarly, kiwifruit with different softening rates were compared, and it was found that the slow softening genotype showed higher concentrations of glucose and xylose, hemicellulose associated components, in the later stages of softening [ 62 ]. This aspect is relevant, given that in cold storage the cell wall continues to undergo modifications that affect fruit firmness.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, fruit firmness is closely associated with changes in the biochemical properties of the cell wall. Polygalacturonase (PG) is a key enzyme involved in cell wall modifications during fruit ripening, with its important functions in degradation of soluble pectin and depolymerization of solubilized pectin [50][51][52]. In kiwifruit, there are three polygalacturonase genes, namely, PGA, PGB, and PGC.…”
Section: Preharvest Application Of Chitosan Maintained the Firmness Of 'Garmrok' Kiwifruit During Cold Storagementioning
confidence: 99%
“…In kiwifruit, there are three polygalacturonase genes, namely, PGA, PGB, and PGC. Of these, PGC is a predominant gene expressed throughout the softening of kiwifruit [50,51,53]. The suppression of the AdPGC gene in preharvest chitosan-treated 'Garmrok' kiwifruit during the early phase of storage (i.e., 30 and 60 days) may be associated with the delayed kiwifruit softening and retained firmness.…”
Section: Preharvest Application Of Chitosan Maintained the Firmness Of 'Garmrok' Kiwifruit During Cold Storagementioning
confidence: 99%
See 1 more Smart Citation
“…At physiological level, the volume of intercellular air spaces was proven to be enlarged while cell wall material shrinked together with reduction of xyloglucan molecular weight [28] , [29] . Furthermore, the activities of critical enzyme, such as XTH, PG, PME, β-Gal were investigated by several reports [19] , [30] , [31] , [32] , [33] , although there seem to be some conflict among them. At molecular level, it was reported that AdXTH5 can be actively regulated by AdEIL2 (EIN3-Like) and AdEIL3 to promote softening [34] .…”
Section: Introductionmentioning
confidence: 99%